2007
DOI: 10.1108/10569210710844390
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among industry environment, diversification motivations and corporate performance

Abstract: Purpose -This paper aims to examine empirically the relationships among industry environment, diversification motivations and corporate performance for a sample of Taiwanese automobile enterprises. Design/methodology/approach -A 55-item survey questionnaire was developed to obtain the responses from companies in the automobile industry in Taiwan. Independent sample t-test and x 2 tests were employed to confirm the homogeneity between the respondents and non-respondents by firm's characteristics, including by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…To support this, in May 2008, the Cross Border Investment Division was introduced under the Malaysian Industrial Development Authority (MIDA). diversification theory (Qian, 1996;Tan et al, 2007). MNCs are able to diversify risk better, allowing them to undertake higher risk, but with a higher return on investment.…”
Section: Introductionmentioning
confidence: 99%
“…To support this, in May 2008, the Cross Border Investment Division was introduced under the Malaysian Industrial Development Authority (MIDA). diversification theory (Qian, 1996;Tan et al, 2007). MNCs are able to diversify risk better, allowing them to undertake higher risk, but with a higher return on investment.…”
Section: Introductionmentioning
confidence: 99%
“…Rather it is seen that as the strategies of diversification ascend to higher levels, that is, from Single Business to Dominant Business to Related Business, the negativity in relationship between diversification strategy and dependent variables becomes more vivid and significant. Even the past research shows mixed results between diversification and performance, as Rhoades (1973), Nathanson andCassano (1982), Nyugen et al, (1990), Farjoun (1998), Tan et al, (2007), show positive association between diversification and performance while Hall (1995), Rogers (2001), George and Kabir (2005), show negative relationship between the two variables. However, Bettis and Hall (1982), , Delios and Beamish (1999) showed no relationship between the strategy of diversification and performance.…”
Section: Discussionmentioning
confidence: 98%
“…Next, concerning product diversification measurement, certain scholars (Pandya & Rao, 1998;Tan, Chang, & Lee, 2007) measured this strategy using Rumelt's (1974) diversification classes, while others depended on using continuous measures such as Diversification Entropy Measure (David, O'Brien, Yoshikawa, & Delios, 2010;Singh, Mathur, Gleason, & Etebari, 2001) or Herfindahl Index (Çolak, 2010;Fukui & Ushijima, 2006). The use of different measurement methodologies for geographic diversification such as foreign sales ratio (Capar & Kotabe, 2003;Geringer, Beamish, & daCosta, 1989), geographic entropy measure (Hitt et al, 1997), along with many others have also been frequently observed in the history of literature on the field.…”
Section: A Comment On Methodologiesmentioning
confidence: 99%